Antifibrotic and anthelminthic effect of casticin on Schistosoma mansoni-infected BALB/c mice - Ho Yin Pekkle Lam; Ting-Ruei Liang; Yi-Chia Lan; Kai-Chih Chang; Po-Ching Cheng; Shih-Yi Peng (Journal of Microbiology, Immunology and Infection, 2022)
Background/Purpose: Schistosomiasis is an important tropical disease caused by Schistosoma. Although the pathogenesis of liver fibrosis has been intensively studied, the choice of effective treatment is still inadequate. In this study, we aimed to investigate the potential of using Casticin to treat Schistosoma mansoni-induced liver fibrosis. Methods: BALB/c mice were divided into three groups – control, infection, and treatment group. The infection and treatment group were percutaneously infected with 100–120 cercariae. Mice from the treatment group were treated with 20 mg/kg/day Casticin for 14 consecutive days to investigate the potential protective effects of Casticin. Mice were sacrificed and were used for histological, RNA, protein, and parasite burden analysis. Results: Our results showed that hepatic fibrosis was significantly attenuated, as indicated by histology and reduction of fibrotic markers such as collagen AI, transforming growth factor β (TGF-β), and α-smooth muscle actin (α-SMA). Furthermore, Casticin treatment significantly reduced worm burden. Anthelmintic effect of Casticin was also observed by scanning electron microscopy. Conclusion: Collectively, our study suggested that Casticin may be a beneficial candidate in treating S. mansoni infection.